2019
DOI: 10.3390/cancers11040470
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of Plasmacytoid Dendritic Cells in Solid Tumors: A Brief Review

Abstract: The immune response, both innate and adaptive, is a key player in cancer development and progression. Plasmacytoid dendritic cells (pDCs) are a subset of dendritic cells that play one of the central roles in the immune system. They are known mostly as the major IFN type I-producing cells upon stimulation of Toll-like receptors 7 and 9. However, based on current knowledge, the functionality of pDCs is very complex, as they have the ability to affect many other cell types. In the context of the tumor tissue, pDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 98 publications
1
54
1
Order By: Relevance
“…Dendritic cells BioMed Research International (DCs) are one of the core components of the immune system responsible for initiating an adaptive immune response that penetrates tumors and processes and presents tumor-derived antigens to naive T cells [35]. DC plays a key role in eliciting antitumor T cell immunity and thus represents the primary therapeutic target for cancer immunotherapy [36,37]. Mast cells (MC) are thought to be involved in the regulation of innate and adaptive immune responses [38].…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells BioMed Research International (DCs) are one of the core components of the immune system responsible for initiating an adaptive immune response that penetrates tumors and processes and presents tumor-derived antigens to naive T cells [35]. DC plays a key role in eliciting antitumor T cell immunity and thus represents the primary therapeutic target for cancer immunotherapy [36,37]. Mast cells (MC) are thought to be involved in the regulation of innate and adaptive immune responses [38].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a marked difference in dendritic cell (DC) subsets. First, conventional type 2 dendritic cells (cDC2), plasmacytoid dendritic cells (pDC) and mature regulatory dendritic cells (mregDCs) (60)(61)(62), which can suppress anti-tumor immunity in certain contexts, were prominent DC subtypes in treatment-naïve samples, but absent from CRT specimens (Figure 2A) (63). In contrast, conventional type 1 dendritic cells (cDC1), which activate cytotoxic lymphocytes critical for anti-tumor immunity, was the only DC subset detected in post-CRT tumors (Figure 2A).…”
Section: Neoadjuvant Treatment Has Implications For Anti-tumor Immunitymentioning
confidence: 99%
“…Moreover, rlipoE7m plus POCpG/DOTAP combined reduced the number of tumor-infiltrating regulatory T cells dramatically due to downregulation of IL-10 production by DCs. These results showed that the combination of rlipoE7m plus POCpG/DOTAP could target DCs via intravenous delivery to enhance antitumor immunity and reduce the number of immunosuppressive cells in the tumor microenvironment.Cancers 2020, 12, 810 2 of 15 (PRRs), such as toll-like receptors (TLRs) and nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs) [8,9]. Thus, the adjuvanticity of PAMP-derived immunostimulators can promote tumor-associated antigen-induced antitumor immunity [10].…”
mentioning
confidence: 99%
“…Cancers 2020, 12, 810 2 of 15 (PRRs), such as toll-like receptors (TLRs) and nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs) [8,9]. Thus, the adjuvanticity of PAMP-derived immunostimulators can promote tumor-associated antigen-induced antitumor immunity [10].…”
mentioning
confidence: 99%